2017
DOI: 10.1177/0046958017707295
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Adaptation and Validation of the Attitudes Toward Suicide Questionnaire Among Healthcare personnel in Malaysia

Abstract: Understanding attitudes toward suicide, especially among healthcare personnel, is an important step in both suicide prevention and treatment. We document the adaptation process and establish the validity and reliability of the Attitudes Toward Suicide (ATTS) questionnaire among 262 healthcare personnel in 2 major public hospitals in the Klang Valley, Malaysia. The findings indicate that healthcare personnel in Malaysia have unique constructs on suicide attitude, compared with the original study on a Western Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…This was what happened in a cross-cultural study of Attitude toward Suicide Questionnaire. Researchers found that the data taken from Malaysian respondents produced unequal amount of factors as compared with the original study in Western population [14]. Similar findings also obtained in earlier cross-cultural study on psychological instruments in Malaysia such as in Ng, Trusty & Crawford, [15], Ramli, Mohd Ariff, & Zaid [16] and Oei, Sukanlaya, Goh & Firdaus, [17].…”
Section: Introductionsupporting
confidence: 65%
“…This was what happened in a cross-cultural study of Attitude toward Suicide Questionnaire. Researchers found that the data taken from Malaysian respondents produced unequal amount of factors as compared with the original study in Western population [14]. Similar findings also obtained in earlier cross-cultural study on psychological instruments in Malaysia such as in Ng, Trusty & Crawford, [15], Ramli, Mohd Ariff, & Zaid [16] and Oei, Sukanlaya, Goh & Firdaus, [17].…”
Section: Introductionsupporting
confidence: 65%
“…60 The KMOs of the 3 scales were 0.807, 0.916, and 0.745. According to previous studies, 61,62 factor loading values at 0.3 or greater can be considered acceptable, and factor loading greater than 0.55 can be considered good. Table 1 shows that all the loading values of the items corresponding to the dimensions are greater than 0.55, and the total variances explained by each of the three scales are 56.38%, 66.12%, and 62.91%, respectively, indicating an acceptable and good construct validity.…”
Section: Methodsmentioning
confidence: 96%
“…The DASS 21 has been translated and validated among Vietnamese women [42] and adolescents [43]. The reliability and validity of DASS 21 among health care and nursing populations had been widely reported [44, 45]. In this study, the Cronbach alphas based on standardized items for the whole scale, DASS 21-stress, DASS21-anxiety and DASS 21-depression were 0.89, 0.78, 0.74 and 0.74, respectively.…”
Section: Methodsmentioning
confidence: 99%